Advertising and differentiated products - Heene, Aimé; Martens, Rudy; Sanchez, Ron; Baye, Michael R., 1958-; Nelson, Jon P. (Emerald, 2001)
This volume of papers develops the competence perspective on learning and dynamic capabilities development. The first two papers explore how organizational competence and dynamic capabilities can support the competitive position of a firm. The next two papers are devoted to strategic, organizational, and behavioral perspectives on processes of competence development. The final four papers explore the intellectual challenges that managers face in striking a strategic balance between processes of competence building and competence leveraging. Taken together, the papers in this volume provide a bridge between many traditional management concepts, frameworks, and theoretical perspectives.
Keywords: Business & Economics -- Strategic Planning.; Business & Economics -- Management Science.; Personnel & human resources management.; Microeconomics.; Advertising.; elektronické knihy; electronic books